2002
DOI: 10.1046/j.1532-5415.2002.50060.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Treatment on Sleep and Circadian Rhythms in Demented Nursing Home Patients

Abstract: OBJECTIVES-To determine whether fragmented sleep in nursing home patients would improve with increased exposure to bright light. DESIGN-Randomized controlled trial. SETTING-Two San Diego-area nursing homes.PARTICIPANTS-Seventy-seven (58 women, 19 men) nursing home residents participated. Mean age ± standard deviation was 85.7 ± 7.3 (range 60-100) and mean Mini-Mental State Examination was 12.8 ± 8.8 (range 0-30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
253
2
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(276 citation statements)
references
References 51 publications
(60 reference statements)
9
253
2
6
Order By: Relevance
“…The old age, severity of dementia, and large inter-individual differences in our sample may also explain, in part, the lack of treatment effects. It is possible that subjects respond to light differently across the lifespan and range of cognitive impairment (Yamadera et al, 2000;Ancoli-Israel et al, 2002). Since 96% of our sample scored in the moderate or severe range of MMSE scores, subjects may have had only a weak sensitivity to the light exposure as suggested by Yamadera et al (2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The old age, severity of dementia, and large inter-individual differences in our sample may also explain, in part, the lack of treatment effects. It is possible that subjects respond to light differently across the lifespan and range of cognitive impairment (Yamadera et al, 2000;Ancoli-Israel et al, 2002). Since 96% of our sample scored in the moderate or severe range of MMSE scores, subjects may have had only a weak sensitivity to the light exposure as suggested by Yamadera et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have used similar methods to define day and night intervals (e.g. Ancoli-Israel et al, 2002) and these methods correlate well with actual nurse recorded time in bed. For example, Fetveit and colleagues (2003) reported actual time in bed to be approximately 12 hours in a study of 11 patients with dementia who participated in a light study.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have focused primarily on dementia sufferers with greater effects observed when combined with melatonin [38]. By contrast, some studies have seen little effect of light therapy on sleep of demented care home residents [39][40][41][42]. Bright light has also been shown to improve the sleep and cognitive performance of older people living in the community not suffering from dementia [43].…”
Section: Introductionmentioning
confidence: 99%
“…In randomizedcontrolled trials, long-term care residents exposed to bright light showed improved sleep relative to participants who received placebo interventions. 21,22,35,36 Researchers have also examined the effectiveness of supplemental melatonin (a hormone, typically secreted at night, that is closely linked to sleep), but results are mixed. Several aspects of the use of melatonin to improve sleep in long-term care residents, specifically, administration timing, dose, and preparation (acute vs. sustained release) are not clear.…”
Section: Non-pharmacological Treatment Of Sleep Problemsmentioning
confidence: 99%